Understanding and influencing agency and behaviour change in Kenya - Guettou Djurfeld, Nadia; Mathenge, Catherine; Ndiwa, Aurillia M.; Magaju, Christine; Voss, Rachel C.; Freed, Sarah (2023)
This country brief is part of the outputs for Work Package 5 of the CGIAR Initiative on Agroecology. The focus of Work Package 5 is understanding and then influencing individual and collective agency and behavior among food system actors (FSAs) to drive inclusive and equitable agroecological transformation. Through learning from past experiences relevant to agroecological transformation, this country brief aims to inform the development of the Agroecological Living Landscapes (ALL) and the approach to the Agroecology Initiative’s (AE-I's) activities in Kenya. The aim is to investigate successes and failures in achieving behaviour change, the nature of the change(s) achieved as well as the aims and assumptions behind the actions planned to enable change. The country brief outlines the trends in initiatives that make a significant contribution to agroecological transformation in terms of numbers of initiatives, types of initiatives, and AE principles promoted.